Strategi Struktur Organisasi Hybrid dan Dampaknya terhadap Keterlibatan Karyawan, serta Kemampuan Beradaptasi dalam Transformasi Digital: Systematic Literature Review - Jusuf, Halid K; Alhidayatullah, Alhidayatullah; Aziz, Muh. Abdul; Purwana, Dedi; Mukhtar, Saparuddin; Suparno, Suparno (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to provide a comprehensive understanding of the context and theoretical foundations used in organizational structures that impact employee engagement and adaptability in digital transformation. This study uses the PRISMA systematic review method by analyzing 15 empirical articles on organizational structure, employee engagement, and adaptability in digital transformation from 2017 to 2024 and from various countries. A brief description and recommendations for future research agendas are also presented for each theory applied. Despite the breadth of the results of previous studies, this review shows that most studies investigate the formation of organizational structures by involving employees in them. Furthermore, the theories used, such as agile theory, transformational leadership theory, and resilience theory, highlight the importance of organizational agility, adaptive leadership, and organizational resilience. This research contributes to stakeholders and shareholders in formulating the right organizational structure for the sustainability of the Company, in addition to adding references for future researchers who will conduct literature studies related to organizational structure, employee involvement, and adaptability in digital transformation.